Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.icarus.2014.03.024
|View full text |Cite
|
Sign up to set email alerts
|

The discovery and dynamical evolution of an object at the outer edge of Saturn’s A ring

Abstract: We report on the serendipitous discovery of an unresolved, evolving, sub-km-radius object with a semimajor axis < 10 km inside that of the edge of Saturn's main rings. The object has been detectable in Cassini images since at least May 2012 and its changing orbit shows evidence of a possible disruption in early 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…In (Spitale and Porco(2010)), we identified at least 2 non-periodic perturbations (referred to as "spikes") in the B-ring edge that moved at Keplerian rates, suggesting the presence of mass concentrations internal to the ring, close enough to the edge to produce observable radial anomalies. A similar disturbance had also been noted at the A-ring edge (Spitale and Porco(2009)), and more recently an object has been directly imaged on that edge (Murray et al(2014)). The irregular appearance of the Huygens ringlet suggests the presence of many such mass inhomogeneities.…”
Section: Irregular Structuresupporting
confidence: 62%
“…In (Spitale and Porco(2010)), we identified at least 2 non-periodic perturbations (referred to as "spikes") in the B-ring edge that moved at Keplerian rates, suggesting the presence of mass concentrations internal to the ring, close enough to the edge to produce observable radial anomalies. A similar disturbance had also been noted at the A-ring edge (Spitale and Porco(2009)), and more recently an object has been directly imaged on that edge (Murray et al(2014)). The irregular appearance of the Huygens ringlet suggests the presence of many such mass inhomogeneities.…”
Section: Irregular Structuresupporting
confidence: 62%
“…These migrating propeller-shaped structures (85), an analogy for protoplanets forming in a planetary nebula, were followed during the mission. Cassini also witnessed signs of the possible formation of a new moon at the outer edge of Saturn's A ring (86).…”
Section: Ringsmentioning
confidence: 99%
“…We showed that the object Peggy recently discovered at the ring edge (Murray et al 2014) is strongly perturbed by the Janus 7:6 LER (when Janus is on its inner leg of its libration motion), but not currently perturbed by any CER, with fitted semi-major axes just outside one of the four chaotic radial zones ( Figure 6). The model presented suggests that the periodic CER/LER perturbations due to the co-orbital moons may help to form objects at the ring edge from particles that move outwards.…”
Section: Discussionmentioning
confidence: 74%